The Application of JENDL-5.0 Covariance Libraries to the Keff Uncertainty Analysis of the HTTR Criticality Benchmark - Peng Hong Liem (Journal of Nuclear Engineering)
In this study, a 56-group covariance library was generated based on the recently released JENDL-5 covariance data, which cover 105 isotopes. The AMPX-6 code system facilitated the generation of this library. Subsequently, the TSUNAMI-IP code was employed to estimate the uncertainty in the effective neutron multiplication factor (keff) for the critical experiment conducted in the Japanese High-Temperature Test Reactor (HTTR). Our analysis involved comparing results obtained from three nuclear data libraries: JENDL-5, ENDF/B-VIII.0, and ENDF/B-VII.1. The keff uncertainty originated from the nuclear data of JENDL-5, ENDF/B-VIII.0, and ENDF/B-VII.1 and were estimated to be 0.387%, 0.581%, and 0.556%, respectively. Interestingly, when the JENDL-5 covariance library was combined with ENDF/B-VIII.0 for JENDL-5 nuclides lacking covariance data, the keff uncertainty increased to 0.464%. The primary contributors to the keff uncertainty, ranked in decreasing order, were U-235 (nubar), C-12 (n,gamma), U-235 (fission), C-12 (elastic), and U-238 (n,gamma). Notably, significant differences in the keff uncertainty were observed between JENDL-5 and ENDF/B-VIII.0, particularly for U-235 (nubar) and C-12 (elastic). Additionally, the sensitivity coefficients, similarity, and kinetics parameters were evaluated across the three libraries, leading to insightful inter-library comparison results.